Magnetic Resonance-Guided Diagnosis of Spontaneous Intracranial Hypotension in a Middle-Aged Woman - Jordan Hughes; Briana Chavez (Case Reports in Neurological Medicine)
Spontaneous intracranial hypotension (SIH) is a rare condition caused by a cerebrospinal fluid (CSF) leak. It is diagnosed by clinical features that include an orthostatic headache combined with imaging findings demonstrating intracranial hypotension and a CSF leak. We present the case of a 45-year-old woman with an orthostatic headache who was found to have a sagging brain with a downward-displaced cerebellum and pachymeningeal enhancement with gadolinium contrast. This was initially misidentified as a Chiari I malformation, but the constellation of symptoms and MRI findings were later recognized as characteristic of SIH. Diagnosis of SIH and a CSF leak was confirmed with CT myelography. She was treated with a nontarget epidural blood patch, and her symptoms resolved. An orthostatic headache, a sagging brain, and pachymeningeal enhancement on MRI are highly specific for SIH, raising suspicion for this uncommon and often missed diagnosis.